Genetic analysis of medaka fish illuminates conserved and divergent roles of Pax6 in vertebrate eye development - Mikula Mrstakova, Simona; Kozmik, Zbynek (Frontiers in Cell and Developmental Biology, 2024)
Landmark discovery of eye defects caused by Pax6 gene mutations in humans, rodents, and even fruit flies combined with Pax6 gene expression studies in various phyla, led to the master control gene hypothesis postulating that the gene is required almost universally for animal visual system development. However, this assumption has not been broadly tested in genetically trackable organisms such as vertebrates. Here, to determine the functional role of the fish orthologue of mammalian Pax6 in eye development we analyzed mutants in medaka Pax6.1 gene generated by genome editing. We found that transcription factors implicated in vertebrate lens development (Prox1a, MafB, c-Maf, FoxE3) failed to initiate expression in the presumptive lens tissue of Pax6.1 mutant fish resulting in aphakia, a phenotype observed previously in Pax6 mutant mice. Surprisingly, the overall differentiation potential of Pax6.1deficient retinal progenitor cells (RPCs) is not severely compromised, and the only cell types affected by the absence of Pax6.1 transcription factor are retinal ganglion cells. This is in stark contrast to the situation in mice where the Pax6 gene is required cell-autonomously for the expansion of RPCs, and the differentiation of all retina cell types. Our results provide novel insight into the conserved and divergent roles of Pax6 gene orthologues in vertebrate eye development indicating that the lens-specific role is more evolutionarily conserved than the role in retina differentiation.